Macroeconomic Modeling of Managing Hurricane Damage in the Caribbean : The Case of Jamaica - Burns, Andrew; Jooste, Charl; Schwerhoff, Gregor (World Bank, Washington, DC, 2021)
This paper describes a modeling methodology that embeds climate damages from natural disasters and risk management strategies into a macroeconomic model for Jamaica. The modeled damages take the form of capital destruction, and the risk management strategies considered are (i) adaptation investment in hurricane resilient infrastructure, (ii) commercial disaster insurance for the government, (iii) the formation of a contingency fund, and (iv) lower debt via higher future primary balances to create fiscal space for disaster recovery. Different risk management strategies are compared to a baseline of no risk management. The model behavior is estimated empirically on country-specific data. Hurricane damage and the model results are analyzed in deterministic and probabilistic settings, using the historical distribution of damages for Jamaica.